Calcium signaling in astrocytes and gliotransmitter release - Goenaga, Julianna; Araque, Alfonso; Kofuji, Paulo; Herrera Moro Chao, Daniela (Frontiers in Synaptic Neuroscience, 2023)
Glia are as numerous in the brain as neurons and widely known to serve supportive roles such as structural scaffolding, extracellular ionic and neurotransmitter homeostasis, and metabolic support. However, over the past two decades, several lines of evidence indicate that astrocytes, which are a type of glia, play active roles in neural information processing. Astrocytes, although not electrically active, can exhibit a form of excitability by dynamic changes in intracellular calcium levels. They sense synaptic activity and release neuroactive substances, named gliotransmitters, that modulate neuronal activity and synaptic transmission in several brain areas, thus impacting animal behavior. This “dialogue” between astrocytes and neurons is embodied in the concept of the tripartite synapse that includes astrocytes as integral elements of synaptic function. Here, we review the recent work and discuss how astrocytes via calcium-mediated excitability modulate synaptic information processing at various spatial and time scales